Análisis de la cinética de flotación en celda convencional de material aurífero de la veta “San Salvador” de la mina PROMINE CIA LTDA, Camilo Ponce Enríquez – Azuay - Sanango Zaruma, Harman Leonardo (2023)
In this study, the flotation kinetics of a gold sample obtained from the PROMINICE CIA LTDA plant were calculated. Three different collectors were used in this flotation process, with the percentage of solids kept constant and the flotation times varied. Using the research process, the company was able to determine the optimal extraction time for the "San Salvador" vein. Before calculating the optimum flotation time, laboratory tests were conducted to determine material recovery. The reagents used in the process were Potassium Amyl Xanthate, Sodium Isopropyl Xanthate and Copper Sulfate. The results obtained by testing different concentrations of solids and flotation times in the conventional cell indicated a recovery of 55.39% with the use of Sodium Isopropyl Xanthate as a collector. According to the Garcia-Zuñiga model, a kinetic constant of 0.9852 min-1 was obtained and an optimum time of 0.127 minutes was determined. Meanwhile, the 25% solids fraction, using the same collector, produced a higher recovery. However, the enrichment decreased as the cell time elapsed. Key words: Flotation kinetics, Denver cell, Collector, Auriferous.